MyRedTides a fast and easy web application for sharing Harmful Agal Bloom information in Sabah, Malaysia - Mohammad Noor, Normawaty; Ahmad, Zuhairi; Mustapha, Shuhadah; Ahmad, Sade (2021)
Harmful algal bloom (HAB) was first reported in Sabah coastal waters in 1976. The first event was caused by Pyrodinium bahamense and later in 2005, Margalefidinium polykraikoides started to occur. Since then, these two species have occurred alternately in the risk areas mainly in the West Coast of Sabah and caused huge impact to fisheries industry as well as human health problems. To manage this problem, monthly monitoring has been conducted by the Department of Fisheries Sabah at the affected areas which include 13 districts i.e. Kota Kinabalu, Tuaran, Kota Belud, Sipitang, Tawau, Papar, Kota Marudu, Kudat, Kuala Penyu, Beaufort, Sandakan, Lahad Datu and Semporna. In every district, water samples and shellfish are collected and sent to Likas Fisheries Complex for cell density and toxicity analyses. Data collected from each district are combined to prepare a full report and disseminate to all Fisheries district officers for further action. The whole process of decimating the whole result, took about 3 days. In order to organize and updating data analysis and also to shorten and fast disseminating of HAB data, a Web Apps developed by ArcGIS is being used to develop an application known as MyRedTides for the Department of Fisheries Sabah. Through this application, HAB data can be shared via online public information system and will be used to map and updating HAB information as well as to be employed as early alerting system.